KALIGRAFI ARAB TENTANG KEESAAN ALLAH DALAM KARYASERIGRAPHY - ERGA PONI, Drs. Syafei, M.Ag, Yofita Sandra, S.Pd., M.Pd (Universitas Negeri Padang, 2015)
The word of Calligraphy comes from the French word which calligraphie where as the Greek word meaning called kalligraphia beautiful hand writing. Calligraphy obtain the highest position and is an expression of the spirit of Islam that is very typical. Calligraphy has two main attraction, namely the Al-Quran verses contained there in and the beauty style of letter. Calligraphy that has an appeal that is so high, it is necessary to use the maximum of calligraphy that for a kindness. With so many in this world polytheism Qur'anic verse about oneness of Allah has religious significance as a function to awaken mankind. For this reason, the authors are interested in creating works with the theme